2019
DOI: 10.1007/s12975-018-0683-2
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-Induced MicroRNA-212/132 Alter Blood-Brain Barrier Integrity Through Inhibition of Tight Junction-Associated Proteins in Human and Mouse Brain Microvascular Endothelial Cells

Abstract: Blood-brain barrier (BBB) integrity is one of the important elements of central nervous system (CNS) homeostasis. MicroRNAs (miRs) have been demonstrated to play a role in many CNS disorders such as stroke and traumatic brain injury. MiR-212/132 are highly expressed in the CNS but their role at the BBB has not been characterized yet. Thus, we analyzed the expression of miR-212/132 in hypoxic mouse and human brain microvascular endothelial cells (BMEC) as well as in posttraumatic mouse and human brain tissue an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
68
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(68 citation statements)
references
References 59 publications
(63 reference statements)
0
68
0
Order By: Relevance
“…The integrity of the BBB is determined by the endothelial tight junctions and the basal lamina. While endothelial tight junctions are formed by proteins such as claudin, occludin and zonula occluden (ZO), the basal lamina forms the basement membrane of ECM and includes laminin, collagen, and fibronectin [177,178]. Astrocyte-derived factors including angiopoietin-1 (ANG-1) [179][180][181], sonic hedgehog (SHH) [182][183][184][185], glial-derived neurotrophic factor (GDNF) [186][187][188], retinoic acid (RA) [189][190][191], and IGF-1 [192,193] have been demonstrated to promote recovery of the BBB by protecting endothelial cells and/or enhancing tight junction reassembly, via signaling mediated by their receptors, tie-2, patched-1, GDNF receptor alpha-1 and alpha-2, nuclear RA receptor, and IGF-1 receptor, respectively [78,79] (Table.…”
Section: The Bbb Integrity-promoting Effects Of Astrocytesmentioning
confidence: 99%
“…The integrity of the BBB is determined by the endothelial tight junctions and the basal lamina. While endothelial tight junctions are formed by proteins such as claudin, occludin and zonula occluden (ZO), the basal lamina forms the basement membrane of ECM and includes laminin, collagen, and fibronectin [177,178]. Astrocyte-derived factors including angiopoietin-1 (ANG-1) [179][180][181], sonic hedgehog (SHH) [182][183][184][185], glial-derived neurotrophic factor (GDNF) [186][187][188], retinoic acid (RA) [189][190][191], and IGF-1 [192,193] have been demonstrated to promote recovery of the BBB by protecting endothelial cells and/or enhancing tight junction reassembly, via signaling mediated by their receptors, tie-2, patched-1, GDNF receptor alpha-1 and alpha-2, nuclear RA receptor, and IGF-1 receptor, respectively [78,79] (Table.…”
Section: The Bbb Integrity-promoting Effects Of Astrocytesmentioning
confidence: 99%
“…MiRNAs have been shown to be induced by TBI and therefore may offer therapeutic potential [18]. Previous studies have demonstrated that miR-212 is highly expressed in the brain [19] where it may play a role in synaptic plasticity [20], memory formation [21,22], and blood brain barrier integrity [23]. Meanwhile, this conserved miRNA was shown to be downregulated in Alzheimer's disease (AD), and the tau protein level was increased in the brain of miR-212 knockout mice [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…While the data on the penetration of miRNA from peripheral tissues to the brain are limited, one can assume that this transfer is highly possible, especially during embryonic development when brain tissue and its compartmentalization is not yet fully formed. Moreover, recent experiments performed in two different rodent models has shown that, in certain conditions, such as during hypoxia, miRNAs actively contribute to an increase in the penetrability of the bloodbrain barrier through the inhibition of genes encoding tight junction proteins (Ma et al, 2017;Burek et al, 2019). The role of prenatal and perinatal factors contributing to the risk of schizophrenia was well documented (Kelly and Murray, 2000;Davis et al, 2016).…”
Section: Discussionmentioning
confidence: 99%